Ética e consumo : uma análise dos hábitos de consumo - Gonçalves, Marco Antonio (My University, 2014)
This thesis performs an analysis on the characteristics and patterns of hypermodern society which reinforce and encourage hedonists and individualistic demonstrations turning the human beings into merchandise and generating feelings and attitudes of emptiness and disappointment. It points to the contradictions of the hypermodernity. In the second chapter, it evaluates the real consequences of our behavior as consumers, in terms of environmental sustainability, and it takes reflexion, from the Hans Jonas’s thinking, on the responsibility of every citizen to build values that ensure human well-being and the respect on all kinds of life in its various manifestations. This action of thinking critically and ethically pervades the thoughts of the third chapter, by defending an education to the conscientious consumption, the transformer indicative of this hypermodern society and key element in raising awareness of the population regarding their social responsibility. The consumption is seen as political action, social struggles and claiming new rights that already exist. Only with ethical attitudes and procedures it will be possible to build a fairer society, questioning the values imposed by the consumer society, and seek out new parameters for life in society who are builders of consciousness and ethical attitude.
Realiza-se uma análise ética das características e dos padrões da sociedade hipermoderna que reforçam e incentivam manifestações hedonistas e individualistas transformando o ser humano em mercadoria e gerando sensações e atitudes de vazio e de decepção. Aponta-se para as contradições da hipermodernidade. No segundo capítulo avalia-se as consequências reais de nosso comportamento como consumidores, em função da sustentabilidade ambiental, e reflete-se, a partir do pensamento de Hans Jonas, sobre a responsabilidade de cada cidadão na construção de valores que assegurem o bem-estar humano e o respeito a todas as formas de vida em suas mais variadas manifestações. Esta ação de pensar crítica e eticamente perpassa as reflexões do terceiro capítulo, ao defender uma educação para o consumo consciente, indicativo transformador desta sociedade hipermoderna e elementochave na conscientização da população em relação à sua responsabilidade social. O consumo passa a ser visto como ação política, de lutas sociais e reivindicação de novos direitos já existentes. Somente com atitudes e procedimentos éticos será possível construir uma sociedade mais justa, questionando os valores impostos pela sociedade de consumo, e buscar novos parâmetros para a vida em sociedade que sejam formadores de consciência e atitude ética.
Keywords: Jonas, Hans; Comportamento do consumidor; Sociedade de consumo; Ecologia; Hedonismo